2021
DOI: 10.3390/vaccines9020166
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Calvenza-03 EIV/EHV® Vaccine in Horses: Comparative In Vivo Study

Abstract: Equine influenza (EI) is a highly contagious acute respiratory disease of equines that is caused mainly by the H3N8 subtype of influenza A virus. Vaccinating horses against EI is the most effective strategy to prevent the infection. The current study aimed to compare the kinetics of EI-specific humoral- and cell-mediated immunity (CMI) in horses receiving either identical or mixed vaccinations. Two groups of horses were previously (six months prior) vaccinated with either Calvenza 03 EIV EHV® (G1) or Fluvac In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Inactivated whole virus EI vaccines have been reported to elicit immune responses to both the antigenically variable regions on the viral surface glycoproteins (HA and NA) as well as the more conserved viral proteins such as the NP and M1 matrix protein, believed to induce some level of cross-protection [ 99 , 123 ]. More recently, Pavulraj and coworkers demonstrated that immunization of horses with Calvenza-03 EIV/EHV ® , an inactivated EI vaccine containing Carbimmune ® as an adjuvant, effectively stimulates protective EIV-specific humoral and CMI responses in vaccinated horses [ 124 ]. Specifically, the authors showed that a booster immunization of horses with Calvenza-03 EIV/EHV ® maintained protective antibodies as measured by single radial hemolysis (SRH) for 6 months in vaccinates that received homologous first vaccine dose and 10 weeks when horses received a heterologous first vaccine dose.…”
Section: Inactivated Whole Virus Ei Vaccinesmentioning
confidence: 99%
“…Inactivated whole virus EI vaccines have been reported to elicit immune responses to both the antigenically variable regions on the viral surface glycoproteins (HA and NA) as well as the more conserved viral proteins such as the NP and M1 matrix protein, believed to induce some level of cross-protection [ 99 , 123 ]. More recently, Pavulraj and coworkers demonstrated that immunization of horses with Calvenza-03 EIV/EHV ® , an inactivated EI vaccine containing Carbimmune ® as an adjuvant, effectively stimulates protective EIV-specific humoral and CMI responses in vaccinated horses [ 124 ]. Specifically, the authors showed that a booster immunization of horses with Calvenza-03 EIV/EHV ® maintained protective antibodies as measured by single radial hemolysis (SRH) for 6 months in vaccinates that received homologous first vaccine dose and 10 weeks when horses received a heterologous first vaccine dose.…”
Section: Inactivated Whole Virus Ei Vaccinesmentioning
confidence: 99%
“…Divergence occurred roughly after the appearance of Kentucky/5/2002, California/8560/2002, and Newmarket/5/2003 preC (Figure 1), so that the first full-genome samples from the FC2, FC1 and CIV clades are Richmond/1/2007, Wisconsin/1/2003, ca/Florida/242/2003, respectively. These FC2 and FC1 sequences are currently (or closely match) the EIV formulations frequently manufactured and used for vaccination (29).…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear to what degree low vaccine effectiveness or antigenic mismatch have contributed to recently observed 'breakthrough' outbreaks (20,(24)(25)(26)(27). Recommendations for vaccine formulations are regularly proposed by the World Organization for Animal Health (formerly Office International des Epizooties, OIE) expert surveillance panel (28), but strain inclusion varies in different vaccine formulations (29). The potential for horses to be sources of zoonotic disease given their close association with humans makes EIV an identified neglected disease threat of concern (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Various commercial vaccines and vaccine candidates were developed to control EI in equines including modified live vaccines (MLVs) ( Townsend et al ., 2001 , Youngner et al ., 2001 , Tabynov et al ., 2014 ), whole inactivated vaccines ( Paillot et al ., 2013 , Pavulraj et al ., 2021 ), subunit ( Paillot and Prowse, 2012 ), DNA vaccines ( Soboll et al ., 2003 , Landolt et al ., 2010 ) these antibody responses differ substantially in that particle mediated DNA vaccination does not induce an immunoglobulin A (IgA, recombinant canarypox vector vaccines ( Toulemonde et al ., 2005 ; Paillot et al ., 2006 ), recombinant equine herpesvirus vaccine ( Van de Walle et al ., 2010 ), and reverse genetics-based vaccines ( Ohta et al ., 2021 , 2022 ). The majority of commercially available vaccines in Egypt do not include representatives of FC2 strains.…”
Section: Introductionmentioning
confidence: 99%